The Struggle Of Single Parent: Pattern Of Parenting In The Nuclear Family - Eko Sulistiono; Mustakim Mustakim; Ester Yambeyabdi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
The family is the first place for children to get an education. Through the parents, the educational process is important values for the development of the child. Children will learn about the values of moral, spiritual, and ethical through parents. These values develop along with growing up of children. Therefore, the pattern of parenting becomes important values in delivering identity of the child to adulthood. The above conditions will occur in intact families but unlike the single parent family. Children who are raised by single parents feared to bring harm to the child's development, or education. Thus, a single parent will struggle to do the maximum care, in order to dispel such concerns.Based on that researchers aim to conduct an analysis of parenting within the nuclear family (single parent). The implication of this study is to determine the pattern of education and guidance to children. This study used a qualitative approach with research subjects a single parent that has school-age children. Based on the analysis of research data which obtained the findings that: (1) single parent education related to parent's responsibilities to children, teaching methods applied in family environment, educational tools used and values education, and (2) parental guidance to children tend to religious guidance, social, academic, career and motivation.